Implementation of Javanese Cultural Values in the Professional Ethics of Public Accountants in Public Services - Muhammad Aras Prabowo; Brilliany Asa Dinasti Utomo Putri; Mariska Nur Hanifah (Trescode Green Organization, 2025)
Indonesia, as a diverse country with a rich array of ethnic groups, cultures, and languages, includes Javanese as a significant component in daily social interactions. The preservation of Javanese culture, which encompasses values such as guyub rukun, toto kromo, and gotong royong, plays a crucial role in the ethics of public accounting professions. This study aims to integrate Javanese cultural values into the ethics of public accountants and explore their impact on the quality and integrity of public service. The research employs a qualitative approach using case studies to analyze the application of Javanese cultural values in accounting ethics. The findings indicate that these values can strengthen key ethical principles in accounting professions, such as integrity, objectivity, competence, professionalism, and confidentiality. The integration of Javanese cultural values into public accounting practices enhances service quality and builds public trust. The study suggests that incorporating Javanese cultural values into the professional ethics code can foster a harmonious and professional work environment, ensuring fair and high-quality public service. Therefore, it is crucial to continue promoting these ethical values to strengthen public governance and improve service quality in the future.